The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1519-69842008000300002
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of litterfall and leaf decomposition in a cerrado site

Abstract: We investigated annual litterfall and leaf decomposition rate in a cerrado site. We collected woody plant litter monthly from April 2001 to March 2002 and from July 2003 to June 2004. We placed systematically 13 litter traps (0.5 x 0.5 m) in a line, 10 m one from the other. We sorted litter into 'leaves', 'stems', 'reproductive structures', and 'miscellanea' fractions, oven-dried them at 80 °C until constant mass and weighed the dry material. To assess leaf decomposition rate, we packed leaves recently shed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 22 publications
4
33
1
5
Order By: Relevance
“…Although the mean annual litter production in ) was more than double that observed for the HSAs and TIAs, it was much lower than the 861 gm −2 and 801 g.m −2 , respectively, estimated for primary and secondary tropical forests in South America (Chave et al 2010). It was also lower than the 568 gm −2 and 509 gm −2 reported by Terror et al (2011) and Werneck et al (2001), respectively, for other semideciduous forests in the Ouro Preto region, as well as the 560 gm −2 and 565 gm −2 reported by Valenti et al (2008) and Cianciaruso et al (2006), respectively, for the cerradão (woodland savanna), although it was comparable to the 470 gm −2 and 433 gm −2 reported by Chave et al (2010) and Röderstein et al (2005), respectively, for upland forest formations on cambisols.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Although the mean annual litter production in ) was more than double that observed for the HSAs and TIAs, it was much lower than the 861 gm −2 and 801 g.m −2 , respectively, estimated for primary and secondary tropical forests in South America (Chave et al 2010). It was also lower than the 568 gm −2 and 509 gm −2 reported by Terror et al (2011) and Werneck et al (2001), respectively, for other semideciduous forests in the Ouro Preto region, as well as the 560 gm −2 and 565 gm −2 reported by Valenti et al (2008) and Cianciaruso et al (2006), respectively, for the cerradão (woodland savanna), although it was comparable to the 470 gm −2 and 433 gm −2 reported by Chave et al (2010) and Röderstein et al (2005), respectively, for upland forest formations on cambisols.…”
Section: Discussioncontrasting
confidence: 52%
“…We showed that the miscellaneous fraction of litter production was correlated with rainfall in all habitats (R 2 >0.42) and that the peaks in that fraction occurred mainly at the beginning of the rainy season (in October, November and December). After the leaf fraction, fragments of branches and trunks are the largest contributor to total litterfall in an ecosystem (Martins & Rodrigues 1999, Dent et al 2006Cianciaruso et al 2006, Köhler et al 2008, Valenti et al 2008. During the dry season, twigs and branches can show xylem cavitation, which results in death from embolism (Tyree & Sperry 1989).…”
Section: Discussionmentioning
confidence: 99%
“…According to Delitti (1995), litterfall productions will have distinct relationships with rainfall patterns depending on the ecosystems in question. In Atlantic Forest and restinga (coastal, sandy soil vegetation) areas the greatest deposition of organic material occurs during the rainy season, while the greatest deposition in Cerrado and Caatinga areas occurs during the dry season (Delitti, 1995;Valenti et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, on larger scales, both climatic variables and plant functional traits control it (Cornwell, 2008). The decomposition rate tends to increase from open to closed cerrado physiognomies (Cianciaruso et al, 2006;Valenti et al, 2008). If species occurring in different physiognomies present different traits, we may expect the functional diversity and decomposition rate to be correlated on a regional scale.…”
Section: Traitmentioning
confidence: 99%